The Cultural Perceptions of Healthy Eating in Mexican American Children: A Focused Ethnography. (May 2021) - Ribar, Alicia K.; Kilanowski, Jill F.; Zoucha, Rick
Introduction: Obesity in Mexican American children is reaching epidemic proportions. Improved understanding of children's healthy eating perceptions in culturally diverse populations is needed. The purpose was to describe the meanings and experiences associated with healthy eating from the perspective of Mexican American children.Methodology: The design was a focused ethnography. Midwestern children, aged 11 to 13 years, were interviewed in home and school settings. Leininger's four phases of qualitative data analysis was used to analyze data. Parental consent/child assent was obtained.Results: Twenty-one children were interviewed. Two themes emerged: (a) Mexican American children connect healthy eating with familiar foods in the context of their ethnic culture; and (b) foods that provide feelings of happiness and well-being are associated with healthy eating.Discussion: This study provides a clear understanding of the meaning and perceptions of healthy eating from the perspective of Mexican American children and offers data to promote culturally congruent care.